Devir violão: quando infância e filosofia se tocam... - Santos, Fulvio Barreira Vicente (2022)
What can a philosophy teaching that allows itself to be touched by childhood? Can philosophy be played by children as a guitar is played by a musician? What resonates between childhood and philosophy at school? Our work aims to explore the meanings that emerge from experiences lived between childhood and philosophy in the daily life of a school classrooms and in the experiences lived by a philosophy teacher with children, from the Municipal Education Network of São Mateus- ES. We seek to bring what happens and what happens to us, not to explain or substantiate our practices, but to think, to make public and to dialogue with the resonances between childhood and philosophy found in school. Inspired by elements present in the cartographic research of Kastrup, Passos, Barros, in the concept of excavator by Walter Benjamin and in the perspective of research as an ascetic exercise by Masschelein and Simons, we trace our theoretical-practical-methodological paths, which lead us through our fugue-graphies. We work on the concepts of becoming-guitar, based on Deleuze and Nancy; experience, drinking at Larrosa; childhood inspired by Kohan. We compose a kind of map with narratives of events that crossed and (trans)formed the philosophy teacher and his practices in philosophy teaching. Our study aims to perceive more welcoming, sensitive and inventive possibilities of doing, living and inhabiting education between childhood and philosophy at school.